Computational design, synthesis and evaluation of caffeine imprinted molecular imprint polymer (MIP) - Nurul Maisyarah Samsudin (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
Caffeine is the main active ingredient in coffee where it has stimulating effect on human by increasing mental performance and brain activities. The taste and flavor of coffee depends on the caffeine concentration inside the coffee. Molecular imprinting polymer is one of the approaches to lock and key, which is the concept of preparing substrate-selective recognition sites in a matrix by using a molecular template. In this study, the MIPs were prepared by bulk polymerization and characterized by rebinding experiment. To analysis the caffeine concentration, the step involved are computational design, synthesis and rebinding assay of caffeine. Computational design that used to simulate the polymer properties through molecular modeling and thermodynamic calculations was perform using HyperChem 6.0 software. The molecular modeling with the use of AM1 (Austin Method 1) of semi empirical method with Polak-Ribiere algorithm was used to identify the best candidates for the molecular imprinting of caffeine. Based on the binding energy of modeling data obtained, ratio 3, 4 and 5 of functional monomer over template were expected to have good binding capability in synthesis. The rebinding assay of the synthesized polymer showed that the ratio 4 having high binding selectivity of caffeine with 86% caffeine was absorbed in the MIP.